Biomechanics in Paralympics: Implications for performance - Morriën, F.; Taylor, M. J. D.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To provide an overview of biomechanical studies in Paralympic research and their relevance for performance in Paralympic sports.